Выбор параметров метода повышения качества визуализации маммограмм - Филатова, А.Е. (Кибернетика и вычислительная техника, 2016)
Рассмотрена задача выбора вида и параметров сигмоидальной функции нелинейного контрастирования метода повышения качества визуализации маммограмм IMRI-MAM, а также выбора критерия оценки качества изображения. Выполнена экспериментальная проверка визуального качества обработанных цифровых маммограм с помощью предложенного критерия. Розглянуто задачу вибору виду і параметрів сигмоїдальной функції нелінійного контрастування методу підвищення якості візуалізації мамограм IMRI-MAM, а також вибору критерію оцінки якості зображення. Виконано експериментальну перевірку візуальної якості оброблених цифрових мамограм за допомогою запропонованого критерію. In this article properties of different types of sigmoidal functions are examined. The sigmoidal function of exponential form is proposed to use in the IMRI-MAM method. The properties of exponential sigmoid function are investigated. Optimization of parameters of nonlinear function of contrast enhancement in the IMRI-MAM method is performed. Dependence of the parameters of the sigmoid function of nonlinear contrast enhancement from the statistical characteristics of processed image is shown. The analytical expressions for calculating the parameters of the sigmoid function are found. Brightness, contrast and completeness of brightness gradations are selected as parameters for assessing of image quality. Local criteria for assessing of the image quality are reviewed. An integral criterion of image quality based on the properties of reviewed local criteria is proposed.